Management of Postoperative Atrial Fibrillation and Subsequent Outcomes in Contemporary Patients Undergoing Cardiac Surgery: Insights From the Society of Thoracic Surgeons CAPS‐Care Atrial Fibrillation Registry. Issue 1 (18th December 2013) - Steinberg, Benjamin A.; Zhao, Yue; He, Xia; Hernandez, Adrian F.; Fullerton, David A.; Thomas, Kevin L.; Mills, Roger; Klaskala, Winslow; Peterson, Eric D.; Piccini, Jonathan P.
Abstract Background Postoperative atrial fibrillation (POAF) is a well‐recognized complication of cardiac surgery; however, its management remains a challenge, and the implementation and outcomes of various strategies in clinical practice remain unclear. Hypothesis We hypothesize that treatment for POAF is variable, and that it is associated with particular morbidity and mortality following cardiac surgery. Methods We compared patient characteristics, operative procedures, postoperative management, and outcomes between patients with and without POAF following coronary artery bypass grafting (CABG) in the Society of Thoracic Surgeons multicenter Contemporary Analysis of Perioperative Cardiovascular Surgical Care (CAPS‐Care) registry (2004–2005). Results Of 2390 patients who underwent CABG, 676 (28%) had POAF. Compared with patients without POAF, those with POAF were older (median age 74 vs 71 years, P < 0.0001) and more likely to have hypertension (86% vs 83%, P = 0.04) and impaired renal function (median estimated glomerular filtration rate 56.9 vs 58.6 mL/min/1.73 m2, P = 0.0001). A majority of patients with POAF were treated with amiodarone (77%) and β‐blockers (68%); few (9.9%) underwent cardioversion. Patients with POAF were more likely to experience complications (57% vs 41%, P < 0.0001), including acute limb ischemia (1.0% vs 0.4%, P = 0.03), stroke (4.0% vs 1.9%, P = 0.002), and reoperation (13% vs 7.9%, P < 0.0001). Length of stay (median 8 days vs 6 days, P < 0.0001), in‐hospital mortality (6.8% vs 3.7%, P = 0.001), and 30‐day mortality (7.8 vs 3.9, P < 0.0001) were all worse for patients with POAF. In adjusted analyses, POAF remained associated with increased length of stay following surgery (adjusted ratio of the mean: 1.27, 95% confidence interval: 1.2‐1.34, P < 0.0001). Conclusions Postoperative AF is common following CABG, and such patients continue to have higher rates of postoperative complications. Postoperative AF is significantly associated with increased length of stay following surgery.